From the Storage of Tobacco to a Research Library: The Conversion of the Toulouse Tobacco Factory - Heusse, Marie-Dominique (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Today, Toulouse has got three plain Universities, two polytechnics, as well as a large number of superior schools, mostly dedicated to aeronautics and chemistry. With nearly 100,000 students and a very strong research activity, all university institutions have united to create the Toulouse University Network and the libraries of these universities have built their own documentary network and common catalogue (Toulouse University libraries Network).